The Importance of the Doctrine of the Trinity in Reformed Theology - MOGA, Dinu (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
Discussing the doctrine of the Trinity more recent scholars have shown that the importance of this doctrine in Reformed theology will be understood better when we look at it, not in an isolated position to what was going on in the theological camps before Reformation, but as a part of a theological tradition which precedes Reformation and even the Middle Ages. In Reformed theology the doctrine of the Trinity is also of the greatest importance for the spiritual life of the believer. Quite unjustifiably it is sometimes maintained that the doctrine of the trinity is merely a philosophically abstracted dogma and that it possesses no value for religion and life. But when we believe in the trinity we notice that this doctrine stands in an intimate relationship with our experience as the children of God. We believe that God the Father is the Creator of all things and He supplies for every need of body and soul. He is faithful and Almighty and will do He has promised to do. He has sent the Son who was conceived in Mary by the Holy Spirit. He is our Saviour, who redeemed us with His own blood, died and raised again and is now ascended in glory and constantly intercedes for us with the Father. Christ has sent His Spirit who is working in us and leads us into all truth, preserving us for our eternal inheritance. Thus the confession of the Trinity is the sum of the Christian religion. Without it neither the creation nor the redemption nor the sanctification can be purely maintained. Every departure from this confession leads to error in the other heads of doctrine. We can truly proclaim the mighty works of God only when we recognize and confess them as the one great work of Father, Son and Spirit.